Perioperative Oxidative Stress: The Unseen Enemy. (December 2019) - Stevens, Jia L.; Feelisch, Martin; Martin, Daniel S.
Abstract : Reactive oxygen species (ROS) are essential for cellular signaling and physiological function. An imbalance between ROS production and antioxidant protection results in a state of oxidative stress (OS), which is associated with perturbations in reduction/oxidation (redox) regulation, cellular dysfunction, organ failure, and disease. The pathophysiology of OS is closely interlinked with inflammation, mitochondrial dysfunction, and, in the case of surgery, ischemia/reperfusion injury (IRI). Perioperative OS is a complex response that involves patient, surgical, and anesthetic factors. The magnitude of tissue injury inflicted by the surgery affects the degree of OS, and both duration and nature of the anesthetic procedure applied can modify this. Moreover, the interindividual susceptibility to the impact of OS is likely to be highly variable and potentially linked to underlying comorbidities. The pathological link between OS and postoperative complications remains unclear, in part due to the complexities of measuring ROS- and OS-mediated damage. Exogenous antioxidant use and exercise have been shown to modulate OS and may have potential as countermeasures to improve postoperative recovery. A better understanding of the underlying mechanisms of OS, redox signaling, and regulation can provide an opportunity for patient-specific phenotyping and development of targeted interventions to reduce the disruption that surgery can cause to our physiology. Anesthesiologists are in a unique position to deliver countermeasures to OS and improve physiological resilience. To shy away from a process so fundamental to the welfare of these patients would be foolhardy and negligent, thus calling for an improved understanding of this complex facet of human biology.